Sleep‐related monitoring on awakening mediates the relationship between insomnia‐related interpretive bias and insomnia symptoms using the insomnia ambiguity paradigm. (25th March 2021) - Akram, Umair; Bickle, Eleanor; Howell, Carley; Ozhan, Vildan; Williamson, Jessica; Du Rocher, Andrew
Abstract: A number of studies have examined and confirmed the presence of a sleep‐related interpretive bias amongst poor sleepers and individuals with insomnia using an insomnia ambiguity task. This study explored possible mechanisms underlying the relationship between interpretive bias and insomnia using the insomnia ambiguity task. More importantly, the possible mediating role of sleep‐associated monitoring, sleep preoccupation, sleep anticipatory anxiety and generalized anxiety was also examined. A total of N  = 176 participants were stratified into normal sleepers and those displaying insomnia symptoms. Participants completed an online version of the insomnia ambiguity task and questionnaire measures pertaining to sleep and anxiety. Data concerning task response time and time of testing were also collected. Individuals in the insomnia symptom group presented significantly higher sleep‐related interpretive bias scores compared to normal sleepers. When sleepiness, sleep‐associated monitoring, sleep preoccupation, sleep anticipatory anxiety and generalized anxiety were controlled for, only monitoring on awakening predicted sleep‐related interpretive bias. Multiple mediation modelling demonstrated that sleep‐associated monitoring on awakening mediated the relationship between interpretive bias and insomnia symptoms. The current outcomes are consistent with previous research, supporting the notion that insomnia is characterized by a disorder‐consistent interpretive bias. Furthermore, monitoring for insomnia‐consistent cues on awakening appears to mediate group differences in interpretive bias.